Synthesis and characterization of novel p-type chemically cross-linked ionogels with high ionic seebeck coefficient for low-grade heat harvesting - Sajid, Imran Haider; Aslfattahi, Navid; Sabri, Mohd Faizul Mohd; Said, Suhana Mohd; Saidur, R.; Salleh, Faiz; Nik-Ghazali, Nik Nazri; Hasan, Syed Waqar (Elsevier, 2019)
The low value of the Seebeck coefficient of the order of few μV/K in inorganic conductors, semiconductors and conducting polymers has inspired the researchers to explore alternative thermoelectric materials. In this work, a novel class of ionogels (IGs) has been synthesized with the aim of developing high-performance thermoelectric materials. Chemically cross-linked ionogels were prepared by the immobilization of ionic liquid, 1-butyl-3-methyl imidazolium tetrafluoroborate (BMIMBF4) in polyethylene glycol dimethacrylate (PEGDMA) matrix using azobisisobutyronitrile (AIBN) as the free radical initiator. The concentration of BMIMBF4 in IGs was varied from 60 to 90 wt (wt. %). The impact of variation of ionic liquid content on the thermoelectric properties of ionogels was analyzed by measuring their thermoelectric properties. Thermal stability, glass transition temperature (Tg), Surface morphology, microstructure, the crystallinity of IGs and nature of chemical interaction between the ionic liquid and polymer matrix were observed by performing TGA, DSC, FESEM, FETEM, XRD, and FTIR respectively. The ionic conductivities of neat BMIMBF4 and IGs were determined by electrochemical spectroscopy using SI 1260 Impedance/Gain-Phase Analyzer. It is worth noting that ionic conductivity (49.41 mS/cm) of IG with 90 wt % of BMIMBF4 is 10 times higher than the ionic conductivity of neat BMIMBF4 (4.5 mS/cm). The origin of this promising achievement (very high conductivity) lies in the “breathing polymer chain model”. The breathing in and out of polymer chains dissociates the ion aggregates resulting in a significant increase in ionic conductivity of IGs. A remarkably higher value of the Seebeck coefficient (2.35 mV/K) was achieved for IG with 60 wt % of BMIMBF4 and defined as ionic Seebeck coefficient because of its origin from the diffusion of ions of the ionic liquid. Due to the positive value of ionic Seebeck coefficient (in an analogy to positive Seebeck coefficient of p-type semiconductors) we termed the ionogels as p-type chemically crosslinked ionogels. A decrease in glass transition temperature of IGs with an increase in ionic liquid content was observed from DSC curves corresponding to an increase in mobility of cations and anions. TGA analysis showed that the synthesized IGs were highly thermally stable up to 390 °C. FESEM and FETEM images revealed that ionic liquid is well confined in the PEGDMA scaffold. The results indicate that ionogels may serve as promising candidates for future thermoelectric applications and also opens the perspective of engineering ionogels with high Seebeck coefficients and electrical conductivities. © 2019 Elsevier Ltd